Emerging drugs to treat obsessive–compulsive disorder. (March 2014) - Pallanti, Stefano; Grassi, Giacomo; Cantisani, Andrea
<x xml:space="preserve">Abstract</x> Introduction: Obsessive–compulsive disorder (OCD) is a chronic and disabling neuropsychiatric disorder with a lifetime prevalence of approximately 1 – 2% and a rate of treatment resistance of 40%. Other disorders have been related to OCD and have been grouped together in a separate DSM-5 chapter, hypothesizing the existence of an 'OC spectrum', showing a paradigm shift in the conceptualization of the disorder. Areas covered: A review of the most important and recent neurobiological findings that sustain the hypothesis of a more sophisticated model of the disorder is provided, together with a brief overview of the most relevant pharmacological animal models of OCD and its first-line treatments. Current research goals, new compounds tested and the rationale behind the development of these new pharmacologic agents are then explained and reviewed. Expert opinion: In the past years, no effective novel compounds have emerged for the treatment of OCD, even if many efforts has been made in the study of its neurobiological underpinnings. Relevant changes in the conceptualization of the disorder, suggested by interesting new neurobiological evidences, may result helpful in the development of new treatments.